Research advances in the Foundation Industries: TransFIRe Hub 2024 - Jolly, Mark R.; Black, Sue; Stansfield, Jo; Thakoordin, Mike; Newton, Ciel; Shoaib, Sarfraz; Salonitis, Konstantinos; Sherif, Ziyad; Litos, Lampros; Liyanage, Nipuna; Karwa, Nikhil; Paddea, Sanjooram; et al. (UKRI, 2024)
After three productive years, the TransFIRe project has successfully concluded, achieving significant advancements in the Foundation Industries. Recognising the substantial impact these industries have on both the economy and the environment, TransFIRe was established to foster a collaborative, interdisciplinary approach to their transformation, with a strong focus on sustainability, efficiency, and innovation. Our comprehensive final report highlights the project’s impact on creating innovative materials and processes, contributing to potential energy savings of up to 20% and a 25% reduction in CO2 emissions. In collaboration with International Synergies, TransFIRe facilitated the exploration of over 350 industrial symbiosis opportunities, leading to the diversion of more than 10,000 tonnes of waste from landfill. This effort has resulted in innovative products from waste streams.